Patch mastocytoma with silent history - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
A 1-year-old child was first observed for a dark stain present since birth. The family history was negative for similar lesions and the child was born full term after a normal pregnancy. The mother reported that the lesion was present at birth, had not been preceded by different lesions and never changed in the subsequent months. The dermatological examination (Fig. 1) showed a dark, about 3 cm in diameter spot, with irregular margins, devoid of hair and not infiltrated. The dermoscopic examination showed a uniform brown color in the absence of a melanocytic pattern. The rest of the skin and the other organs did not show any abnormality. However, three minutes after a vigorous rubbing of the patch appeared on its surface irregular wheals (see box in Fig. 1) that led to the diagnosis of mastocytoma. A supplement of history confirmed the absence of redness and swelling in the preceding months.